Analisis Pengaruh Brand Name, Service Quality, dan Promotion Terhadap Keputusan Pembelian Konsumen Pada Miniso Tunjungan Plaza Surabaya - Lidwina RA Sinaga; Natasya Intan Pramanda (Universitas Airlangga, 2018)
ABSTRACTMiddle-class consumers need products of good quality, competitive prices and lifestyle. One of the factors that influence consumer behavior in purchasing is lifestyle. Companies must understand the consumer purchase decision process especially in terms of brand name, service quality and promotion. This research is limited to Miniso outlet in Tunjungan Plaza Surabaya. Research respondents are limited to visitors of Miniso Tunjungan Plaza Suraaya in the 17-35 year age range. The type of this research is quantitative descriptive research and instrument used in the form of questionnaire. Data analysis technique used quantitative descriptive data analysis. The validity of data is obtained through validity and reliability. Based on the analysis of the influence of brand name, service quality and promotion of customer purchasing decisions at Miniso Tunjungan Plaza Surabaya from April to May 2018 the result is Brand Name (X1) has a positive influence on Customer Purchase Decision (Y). Service Quality (X2) has a positive influence on Customer Purchase Decision (Y). Thus, the increase or decrease in customer purchasing decisions can be explained directly by service quality. Promotion (X3) has a positive influence on Customer Purchase Decision (Y).